Numerical Simulation of Solid-Liquid Two-Phase Flow in Non-Clog Pump. Issue 1 (1st August 2022) - Gao, Xiongfa; Wang, Junhua; Lu, Hongzhong; Shi, Weidong; Duan, Junli; Meng, Wanli; Jin, Jiamin
Abstract: This paper mainly based on the CFD numerical simulation method to analyze the solid-liquid two-phase flow of the vortex pump. Three kinds of solid-phase volume concentration and three solid-phase particle diameters were given respectively to carry out the numerical simulation of solid-liquid two-phase flow in the internal flow field of the pump. The distribution of solid particles in the impeller and the lateral cavity were analyzed to study the influence of different solid-phase particle diameters and solid-phase particle concentrations on the pump performance. The results showed that there was no obvious concentration distribution at the junction area between blades and hub. The solid phase concentration on the back is lower than that on the working face. Due to the characteristics of circulating flow in the vortex pump, some particles enter the lateral cavity from the blade working face, and some particles enter the blade back face from the lateral cavity under the action of low pressure on the back and circulating flow. Solid particles are mainly distributed in the center of the cavity and are circularly distributed. The overall fluctuation of the solid phase slip velocity on the working face is not large, while the magnitude of the solid phase slip velocity on the back is relatively disordered.